Local Government Policy In Distribution Of Healthcare Workforce During The Covid-19 Pandemic (Kebumen Regency) - Triyo Rachmadi; Resti Agustina (Prophetic Law Review, 2022)
The main responsibility of the Indonesian government is to protect its citizens, including in the healthcare sector. However, the Government of Kebumen Regency has not fully implemented the responsibility. The research questions are (1) what were the policies of the local government of Kebumen Regency concerning the distribution of healthcare workforce during the COVID-19 Pandemic? (2) How do legal theories address any issues related to the local government policies concerning the distribution of healthcare workforce during the COVID-19 Pandemic? This was a qualitative descriptive study which used a sociological or empirical non-doctrinal method. The study was carried out in Kebumen Regency and the sources consisted of the Head of the Healthcare Agency, one human resource analyst, and one healthcare worker. This study operated under various theories, including Aristotelian political ethics and the will to power by Friedrich Wilhelm Nietzsche. This study found that the regent of Kebumen Regency had not demonstrated concern in distributing healthcare workforce to healthcare facilities during the COVID-19 Pandemic. The policy issued by the government of Kebumen Regency concerning the distribution of healthcare workforce is considered inappropriate. The political ethics theory shows that local government could issue policies concerning the distribution of healthcare workforce regardless of the existing needs for healthcare human resources. The will to power theory shows that local government policies can be considered as either appropriate or inappropriate policy.Keywords: distribution, healthcare workforce, healthcare policy, local government. Kebijakan Pemerintah Daerah Dalam Distribusi Tenaga Kesehatan Selama Pandemi Covid-19 (Kabupaten Kebumen) AbstrakTanggung jawab utama pemerintah Indonesia adalah melindungi warga negaranya, termasuk di bidang kesehatan. Namun, Pemerintah Kabupaten Kebumen belum sepenuhnya melaksanakan tanggung jawab tersebut. Pertanyaan penelitian adalah (1) bagaimana kebijakan pemerintah daerah Kabupaten Kebumen terkait pendistribusian tenaga kesehatan pada masa Pandemi COVID-19? (2) Bagaimana teori hukum menyikapi setiap isu yang terkait dengan kebijakan pemerintah daerah tentang distribusi tenaga kesehatan selama Pandemi COVID-19? Penelitian ini merupakan penelitian deskriptif kualitatif yang menggunakan metode sosiologis atau empiris non-doktrinal. Kajian dilakukan di Kabupaten Kebumen dan narasumber terdiri dari Kepala Dinas Kesehatan, satu orang analis sumber daya manusia, dan satu orang tenaga kesehatan. Studi ini beroperasi di bawah berbagai teori, termasuk etika politik Aristotelian dan keinginan untuk berkuasa oleh Friedrich Wilhelm Nietzsche. Studi ini menemukan bahwa Bupati Kabupaten Kebumen kurang memperhatikan distribusi tenaga kesehatan ke fasilitas kesehatan selama masa pandemi COVID-19. Kebijakan yang dikeluarkan oleh Pemerintah Kabupaten Kebumen tentang pendistribusian tenaga kesehatan dinilai kurang tepat. Teori etika politik menunjukkan bahwa pemerintah daerah dapat mengeluarkan kebijakan tentang distribusi tenaga kesehatan terlepas dari kebutuhan sumber daya manusia kesehatan yang ada. Teori kehendak untuk berkuasa menunjukkan bahwa kebijakan pemerintah daerah dapat dianggap sebagai kebijakan yang tepat atau tidak tepat.Kata Kunci: distribusi, tenaga kesehatan, kebijakan kesehatan, pemerintah daerah.